Community-associated methicillin-resistant Staphylococcus aureus, eastern Argentina - Gardella, Noella Mariel (2008)
Sixty-nine community-associated methicillin-resistant Staphylococcus aureus recovered in 6 healthcare centers from northeastern and eastern Argentina were genotyped by pulsed-field gel electrophoresis. The predominant pulsotype was widely distributed harbored SCCmectype IV and Panton–Valentine leukocidin genes. Representative isolates were characterized by multilocus sequence typing and spa typing, demonstrating that this clone belonged to ST5 and spa type 311.